2019
DOI: 10.1371/journal.pone.0215874
|View full text |Cite
|
Sign up to set email alerts
|

Mining and characterization of novel EST-SSR markers of Parrotia subaequalis (Hamamelidaceae) from the first Illumina-based transcriptome datasets

Abstract: Parrotia subaequalis is an endangered Tertiary relict tree from eastern China. Despite its important ecological and horticultural value, no transcriptomic data and limited molecular markers are currently available in this species. In this study, we first performed high-throughput transcriptome sequencing of two individuals representing the northernmost (TX) and southernmost (SJD) population of P . subaequalis on the Illumina HiSeq 2500 platform. We gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The distribution of motif types varies among plants. The most frequent motif type for Parrotia subaequalis was Di- [39], while the most frequent motif type for Lychnis kiusiana and Dendrocalamus hamiltonii was Tri- [40,41]. In this study, Di-repeats were the most abundant motif (mononucleotides were not considered) in P. lactiflora, and AG/CT accounted for 36.55% of all SSRs, followed by AT/AT (14.78%) and AC/GT (11.97%).…”
Section: Discussionmentioning
confidence: 56%
“…The distribution of motif types varies among plants. The most frequent motif type for Parrotia subaequalis was Di- [39], while the most frequent motif type for Lychnis kiusiana and Dendrocalamus hamiltonii was Tri- [40,41]. In this study, Di-repeats were the most abundant motif (mononucleotides were not considered) in P. lactiflora, and AG/CT accounted for 36.55% of all SSRs, followed by AT/AT (14.78%) and AC/GT (11.97%).…”
Section: Discussionmentioning
confidence: 56%
“…However, the downstream development and identification of usable and researchable polymorphic SSRs is still a manual and time-consuming process [39]. Recently, an integrated procedure called CandiSSR was developed and used to obtain polymorphic SSRs in silico using genomic or transcriptomic sequence data [40]. In the present study, using the bioinformatics pipeline, we identified 811 potential polymorphic SSRs in six sequenced transcriptomes of T. mongolica.…”
Section: Identifying and General Profiling Of Genic Ssrs In T Mongolmentioning
confidence: 96%
“…By comparing our finding with some other SSR development projects performed using CandiSSR, we found a similar polymorphic genic SSRs generation rate among these different studies. For example, 497 polymorphic genic SSRs were identified in the comparison of the transcriptomes representing the northern and southern population of Parrotia subaequalis [40]; and 1663 polymorphic EST-SSRs were identified by comparing the transcriptomes of tea plant and 19 Camellia species [48]. The identified SSRs in these studies were relatively small.…”
Section: Identifying and General Profiling Of Genic Ssrs In T Mongolmentioning
confidence: 98%
See 1 more Smart Citation
“…P. subaequalis is of great value in a variety of aspects. First, this species is a relict living-fossil plant originating from the Tertiary, which may play a significant role in reflecting the phylogeny of Hamamelidaceae (Hao et al 1996;Zhang et al 2019) and the origin of early angiosperms (Li and Tredici 2008;Zhang et al 2021). Second, P. subaequalis yields good timber with fine wood-grain, being hard and heavy (Zhong 2016).…”
Section: Introductionmentioning
confidence: 99%